“Trotzdem! Ein gutes Land” (?). Marianne Fritz’ «Dessen Sprache du nicht verstehst» als radikalste Liquidation des habsburgischen Mythos am Leitfaden seiner Sprechakte: [“Nevertheless! A Good Land” (?). Marianne Fritz’s «Whose Language You Do Not Understand» as a Radical Liquidation of the Habsburg Myth on the Basis of Its Speech Acts] (Studia theodisca, 2018)
This paper explores how Marianne Fritz’s novel Dessen Sprache du nicht verstehst incorporates its sources. On the one hand it traces the many contexts of the novel’s title, which cites Deuteronomy, the fifth Book of Moses. At the same time it interrogates the usage of a quote by Franz Grillparzer, «Es ist ein gutes Land» («It is a good land»), and how it communicates with other quotes within the novel. Thereby the essay develops a unique way of reading the novel, which many still judge to be unreadable.